Maurus, Nadia, Flurina - Zen, Ivo (Alva Film ; TVR ; TSR, 2009)
Verzio FF Submission Every year at the end of summer, scores of Swiss adolescents move from their remote valleys in the Grison Alps to the city of Chur. At the age of fifteen they leave their homes and families to attend the cantonal secondary school. The film portrays three teens during their first year of their much awaited independence - the hopes and delights, fears and disappointments of coming-of-age.